THE ECONOMIC CHAOS IN DEVELOPING COUNTRIES: THE CASE OF LEBANON - Akl Kayrouz; Issam Atala (European Scientific Journal, ESJ, 2015)
Economic studies in recent have been strongly influence by mathematical formulas ignoring to a high degree, the basic specifities and differentiating factors in every state and society. It has been common, by international institutions, such as the IMF, the World Bank and local banks, economists or researches to simply rely on superficial and often inaccurate statistics, revolving around GDP, per capita income, inflation rate and others to formulate economic and financial strategies mainly for the developing countries. The general results have been so far abysmal. Wealth is being accumulated in few hands and poverty stricken social closes are rapidly expanding. This paper focuses on the case of Lebanon to highlight the meaning and effective bases of its development. The Real Estate sector was chosen for the study because it is considered the main engine for development. The hypothesis claims that the ballooning of property prices, in the absence of proper taxation policy and economic strategic planning, is indirectly forcing the country’s youth to emigrate, while the poor class increased to about 60% of the population. The research demonstrates that in the absence of good governance and the rule of law, corruption creeps monopolizing power and finances. The country consequently is heading toward instability, violence and possible chaos. It also proves that statistical data wrongly collected do not lead to development rather prevent or worsen it.